2009
DOI: 10.1128/aem.01649-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR Monitoring of Antibiotic Resistance Genes and Bacterial Pathogens in Three European Artificial Groundwater Recharge Systems

Abstract: Aquifer recharge presents advantages for integrated water management in the anthropic cycle, namely, advanced treatment of reclaimed water and additional dilution of pollutants due to mixing with natural groundwater. Nevertheless, this practice represents a health and environmental hazard because of the presence of pathogenic microorganisms and chemical contaminants. To assess the quality of water extracted from recharged aquifers, the groundwater recharge systems in Torreele, Belgium, Sabadell, Spain, and Nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 42 publications
0
77
1
1
Order By: Relevance
“…The identification of tylosin resistant genes present in enterococci was confirmed by PCR (Bockelmann et al, 2009;Sutcliffe et al, 1996b). Colonies isolated on mE agar from swine manure, soil, tile water samples in each simulation were grown on BHI Agar slants before extraction for PCR analysis.…”
Section: Detection Of Tylosin Resistant Genes By Pcrmentioning
confidence: 97%
See 3 more Smart Citations
“…The identification of tylosin resistant genes present in enterococci was confirmed by PCR (Bockelmann et al, 2009;Sutcliffe et al, 1996b). Colonies isolated on mE agar from swine manure, soil, tile water samples in each simulation were grown on BHI Agar slants before extraction for PCR analysis.…”
Section: Detection Of Tylosin Resistant Genes By Pcrmentioning
confidence: 97%
“…The employment of PCR in detecting resistant genes have been well documented (Baele et al, 2000;Bockelmann et al, 2009;Chen et al, 2007;Dutka-Malen et al, 1995;Kariyama et al, 2000;Ke et al, 1999;Luthje and Schwarz, 2007;Sutcliffe et al, 1996b).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Water is a vector for the transfer of ARGs from human and animal waste into the natural environment (JETACAR 1999;Witte 2000;Chee-Sanford et al 2001;Koike et al 2007;Baquero et al 2008) and the aquatic environment has been identified as a reservoir for antibiotic resistance (Biyela et al 2004;Martinez 2008). Only in recent years has there been increased interest in the prevalence of antibiotic-resistant organisms or genes in waterways and waste water (Zhang et al 2009), although very few studies have investigated highly treated effluent (Bockelmann et al 2009). This research was aimed at evaluating the possible input of antibiotic resistance from a relatively new source -reclaimed water -which has the potential to act as another contamination source back into agriculture.…”
Section: Introductionmentioning
confidence: 99%